TTO strategic entrepreneurship model for strengthening RUs innovation ecosystem - Muhammad Sapah, Roszaimah; Ali, Mass Hareeza; Wan Abdul Rahman, Wan Nurhayati (Human Resource Management Academic Research Society, 2023)
Purpose- This study aims to nurture strategic entrepreneurship within Technology Transfer Office (TTO) for enhancing the entrepreneurial role in enabling successful technology transfer for Research Universities (RUs). This article conducts a synthesis of literature review with systematic method to analyse the roles and responsibilities of TTO in RUs, critical factors to nurture Strategic entrepreneurship in TTO and recommend TTO Strategic entrepreneurship model for strengthening RUs innovation ecosystem. The result shows that TTO with strategic entrepreneurship approaches would create pathways for sustainable entrepreneurial culture to support entrepreneur researcher characteristics for best practices on technology transfer to strengthen the innovation ecosystem in RUs. This study highlights recommendation on TTO strategic entrepreneurship model for strengthening RUs innovation ecosystem in enabling successful technology transfer in Malaysia. This is one of few studies in this topic of commercialization of innovation which has remained unexplored. Future study is projected to include development of a framework for nurturing strategic entrepreneurship within TTO to enhance commercialization of innovation through RUs technology transfer.